Decision support system for selective withdrawal in water supply reservoirs: An approach based on thermal stratification - SOYER, ELİF (My University, 2023)
We consider the problem of determining water withdrawal depth in water supply reservoirs with multilevel intakes in an effective and systematic manner. In the traditional way, operators decide which intake port to use based on their own experience and water samples taken from various depths. Our goal is to provide assistance to operators in the decision-making process and establish a systematic approach for determining the appropriate water withdrawal level in a stratified reservoir. To achieve this, we propose an algorithmic approach as a decision support system for estimating the water withdrawal level. We validate our approach using long-term data collected from a water supply reservoir and compare the results with those of the operator\"s decisions. The results reveal that when the depth tolerance is set to 10 m, the approach and operator\"s decisions match at an 80% rate. However, when the depth tolerance is increased to 15 m, the matching percentage improves to over 90%.
Keywords: Tarımsal Bilimler; Ziraat; Toprak ve Bitki Besleme; Toprak ve Su Muhafazası ve Amenajmanı; Havza Yönetimi; Agricultural Sciences; Agriculture; Soil and Plant Feed; Soil and Water Storage and Management; Watershed Management; SU KAYNAKLARI; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); WATER RESOURCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Su Bilimi ve Teknolojisi; Fizik Bilimleri; Water Science and Technology; Physical Sciences; decision support system; selective withdrawal; thermal stratification; water inlet structure; water quality; water supply reservoirs; QUALITY